2021
DOI: 10.1002/jnr.24948
|View full text |Cite
|
Sign up to set email alerts
|

How do zebrafish (Danio rerio) respond to MK‐801 and amphetamine? Relevance for assessing schizophrenia‐related endophenotypes in alternative model organisms

Abstract: Schizophrenia pathophysiology has been associated with dopaminergic hyperactivity, NMDA receptor hypofunction, and redox dysregulation. Most behavioral assays and animal models to study this condition were developed in rodents, leaving room for species‐specific biases that could be avoided by cross‐species approaches. As MK‐801 and amphetamine are largely used in mice and rats to mimic schizophrenia features, this study aimed to compare the effects of these drugs in several zebrafish (Danio rerio) behavioral a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…On a molecular level, DAergic enhancers, such as amphetamine, may lead to increased tumor necrosis factor α (TNFα) and malondialdehyde (MDA) levels, suggesting ongoing increased inflammatory and oxidative processes [ 16 ]. Similar effects were observed in zebrafish, in which amphetamine was able to alter the oxidative status [ 23 ]. Proteomic analyses conducted by Wearne et al [ 24 ] identified 96 proteins that are differentially expressed in the prefrontal cortex in a rat methamphetamine-based model of sensitization; of these differentially expressed proteins, 20% are connected to schizophrenia pathogenesis and linked to synaptic regulation, protein phosphatase signaling, mitochondrial function, and impairments in the inhibitory gamma-aminobutyric acid (GABA) system.…”
Section: Pharmacological Modelssupporting
confidence: 63%
“…On a molecular level, DAergic enhancers, such as amphetamine, may lead to increased tumor necrosis factor α (TNFα) and malondialdehyde (MDA) levels, suggesting ongoing increased inflammatory and oxidative processes [ 16 ]. Similar effects were observed in zebrafish, in which amphetamine was able to alter the oxidative status [ 23 ]. Proteomic analyses conducted by Wearne et al [ 24 ] identified 96 proteins that are differentially expressed in the prefrontal cortex in a rat methamphetamine-based model of sensitization; of these differentially expressed proteins, 20% are connected to schizophrenia pathogenesis and linked to synaptic regulation, protein phosphatase signaling, mitochondrial function, and impairments in the inhibitory gamma-aminobutyric acid (GABA) system.…”
Section: Pharmacological Modelssupporting
confidence: 63%
“…Zebrafish is increasingly considered as a model organism suitable to study drug-induced behavioral phenotypes relevant to schizophrenia (Gawel et al, 2019; Benvenutti et al, 2021). Figure 3A shows that zebrafish exposed to MK-801 spent less time in the side of the tank where conspecifics were presented, denoting decreased social preference in comparison to control groups (MK-801 main effect: F 1,86 = 29.28, p<0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…In regards to zebrafish, it has been demonstrated that MK-801 induces hyperlocomotion, although it is not clear which neuronal mechanisms might be involved (Menezes et al, 2015; Tran et al, 2016; Benvenutti et al, 2021; Franscescon et al, 2021). Zebrafish increasing use is a great solution to avoid species biases and focus on a robust cross-species approach, aside from being an accessible way to screen for potential novels treatments (Bruni et al, 2016; Burrows and Hannan, 2016; Gawel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish have been used as a model organism for biomedical research in drug discovery, developmental biology, and genetics as it presents high mammalian homology [1]. Zebrafish present rapid development and a relatively long lifespan, being used to investigate the neurobehavioral foundations of various neurological and psychiatric conditions such as epilepsy, Alzheimer's and Parkinson's disease, schizophrenia, and stress-and drug-related disorders [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%